2018
DOI: 10.1155/2018/5859013
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Patterns Analysis in the Supraspinatus Muscle after a Rotator Cuff Tear in a Mouse Model

Abstract: Rotator cuff tear is a muscle-tendinous injury representative of various musculoskeletal disorders. In general, rotator cuff tear occurs in the tendon, but it causes unloading of the muscle resulting in muscle degeneration including fatty infiltration. These muscle degenerations lead to muscle weakness, pain, and loss of shoulder function and are well known as important factors for poor functional outcome after rotator cuff repair. Given that rotator cuff tear in various animal species results in similar patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
1
8
1
1
Order By: Relevance
“…Although our model shows a slow progression of atrophy and fatty infiltration beginning at 6 weeks and progressing to 12 weeks, full transection models show more severe results than ours beginning at 2 to 4 weeks. 31,32 The difference in progression of the disease suggests that this impingement model can be used to accurately mimic the clinical rotator cuff changes that lead to the diagnosis of subacromial pain syndrome, a common clinical problem in active individuals. Furthermore, the gait analysis may help provide key functional outcome measurements for future evaluation of new therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Although our model shows a slow progression of atrophy and fatty infiltration beginning at 6 weeks and progressing to 12 weeks, full transection models show more severe results than ours beginning at 2 to 4 weeks. 31,32 The difference in progression of the disease suggests that this impingement model can be used to accurately mimic the clinical rotator cuff changes that lead to the diagnosis of subacromial pain syndrome, a common clinical problem in active individuals. Furthermore, the gait analysis may help provide key functional outcome measurements for future evaluation of new therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Additional genes relating to adipogenesis identified as correlated with RC radiographic assessments (Shah et al, 2017) were also included. The final lists were compared to other RC transcriptome analyses in other animal models (Lee et al, 2018;Gumucio et al, 2019;Flück et al, 2020) for confirmation of overlap although in more broadly described categories.…”
Section: Gene Pathways Of Interestmentioning
confidence: 99%
“…Currently, few human studies have characterized gene expression in RC muscle after tendon tear and how it relates to the severity of muscle changes (Reardon et al, 2001;Steinbacher et al, 2010;Choo et al, 2014;Chaudhury et al, 2016;Shah et al, 2017;Gibbons et al, 2018a;Ren et al, 2018;Ge et al, 2020;Tashjian et al, 2020), but these data could not be related to a time course neither compared to a healthy control. Gene expression data with two or more time points have been collected in a mouse RC tear model and a rat tenotomy and neurectomy model (Lee et al, 2018;Gumucio et al, 2019;Hu et al, 2019), typically focusing on specific programs and gene overlap over the time series. However, even fewer studies have considered the mechanistic effects of muscle unloading in an animal RC tear model which properly recapitulates the human pathophysiology of fatty infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al, 33 in a study with rats, analyzed 39,429 genes and followed changes in their expression after 1 and 4 weeks of injury and identified that rotator cuff rupture induces the expression of specific genes related to aging, apoptosis, atrophy and transport of fatty acids. The authors associated that many genes that are altered may play a role in the tendon degeneration process after the injury.…”
Section: Rotator Cuff Injurymentioning
confidence: 99%
“…Lee et al, 33 em estudo com ratos, analisaram 39.429 genes e acompanharam as alterações na expressão dos mesmos após 1 e 4 semanas de lesão e identificaram que a ruptura do manguito rotador induz a expressão de genes específicos relacionados ao envelhecimento, apoptose, atrofia e transporte de ácidos graxos. Os autores associaram que muitos genes que estão alterados possam ter um papel no processo de degeneração do tendão após a lesão.…”
Section: Lesão Do Manguito Rotadorunclassified